An Analysis Of The Astrological Decorations On The Portal Of The Mirzo Ulugbek Madrasa (The Journal of Interdisciplinary Human Studies, 2026)
This article offers a synergetic and symbolic analysis of the astrological decorations on the portal (peshtoq) and portal-niche (qanos) of the Mirzo Ulugbek Madrasa on the Registan in Samarkand. It shows that the geometric girih, calligraphic, and vegetal ornaments of the madrasa are not mere decoration but a precise mathematical and cosmological program reflecting Ulugbek’s lifelong devotion to astronomy – encoding stars, galaxies, the seven climes, and a “map of the world” of interconnected gravitational systems. A numbered reading of the qanos composition is provided, interpreting each motif as an astronomical-symbolic element.
Keywords: Mirzo Ulugbek Madrasa; Samarkand; Registan; peshtoq (portal); girih; islimi ornament; astrological decoration; synergetic analysis; astronomy; Islamic architecture